Behavior Change Techniques and the Effects Associated With Digital Behavior Change Interventions in Sedentary Behavior in the Clinical Population: A Systematic Review - Martín-Martín, Jaime; Roldán-Jiménez, Cristina; De-Torres, Irene; Muro-Culebras, Antonio; Escriche-Escuder, Adrian; Gonzalez-Sanchez, Manuel; Ruiz-Muñoz, María; Mayoral-Cleries, Fermin; Biró, Attila; Tang, Wen; Nikolova, Borjanka; Salvatore, Alfredo; et al. (Frontiers in Digital Health, 2021)
Background: Sedentary behavior (SB) negatively impact the health and is high prevalent in the population. Digital behavior change interventions (DBCI) have been developed to modify behaviors such as SB by technologies. However, it is unknown which are the Behavior Change Techniques (BCT) most frequently employed in SB as well as the effect associated to DBCI in this field. The aim of this systematic review was: a) to evaluate the BCT most frequently employed in digital health including all technologies available and interventions aimed at increasing physical activity (PA), reducing sedentary time and improving adherence to exercise in clinical population and b) to review the effect associated to DBCI in this field. Methods: The database used was Medline, completed with Scopus, Scielo and Google Scholar. For the search strategy, we considered the spelling versions of behavior / behavioral, mHealth / eHealth / telemedicine / serious game / gamification. The terms related to PA and SB were included. The criteria for inclusion were randomized clinical trials (RCT), adults, intervention based on digital media and outcome variable lifestyle modification. Michie’s Taxonomy was used to identify BCT. PROSPERO CRD42019138681 study’s number Results : eighteen RCTs were included in the present systematic review, 5 of them healthy adults, and 13 of them with some illness. Studies included 2298 sedendary subjects individuals who were followed up for 5 weeks–3 years. The most used BCT were goal setting, problem solving, review outcomes / goals, feedback on behaviour and outcomes of behaviour, self-monitoring of behaviour, social support, information about health consequences, behaviour practice / rehearsal. The effect associated to DBCI showed improvements among several related to PA; physiologic self-reported and anthropometric outcomes. Conclusion: The BCT most used in digital health to change outcomes related to SB were goals and planning, feedback and monitoring, social support, natural consequences, repetition and substitution. Besides this findings DBCI are influenced by several factor like the type of intervention, patients’ preferences and values or the number of BCT employed. More research is need to determine with precision which DBCI or BCT is the most effective to reduce SB in the clinical population.